PENANAMAN NILAI-NILAI MULTIKULTURAL MELALUI PEMBELAJARAN SOSIOLOGI PADA SISWA SMA NEGERI 1 NARMADA - Khaerul Anam; Hamidsyukrie ZM; Nursaptini Nursaptini; Su'ud Su'ud (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
The aim of this research is to find out and analyze the process of instilling multicultural values ​​and the factors that influence the instillation of multicultural values ​​through sociological learning in students at SMA Negeri 1 Narmada. This research is qualitative research with a case study approach. Data sources were obtained from observations, interviews, documentation, research results show that the instillation of multicultural values ​​through sociological learning in students at SMA 1 Narmada is instilled through content integration, where the teacher integrates multicultural values ​​in the learning material. Then through knowledge construction (Knowladge Construction), where the teacher presents learning materials in class, then answers all questions asked by students. Whether the students are women or men, Muslim or non-Muslim, it helps students in the process of understanding the learning material. And finally through equal pedagogy (Equity Pedagogy), where teachers treat all students equally, regardless of gender, religion, race or culture of the students.